Consumer understanding and use of country‐of‐origin in food choice. Issue 1 (2014) - ,; ,
<x xml:space="preserve">Abstract</x> Purpose – This study aimed to investigate consumers' understanding of country of origin (CoO) information and its relative importance in the context of their everyday food purchase decisions. Design/methodology/approach – A cross‐sectional intercept survey of 402 consumers in two cities in New Zealand was conducted. Respondents were asked to describe what they had considered when selecting a food item in their trolley. This was followed by questions to assess respondents' knowledge of CoO and their use and understanding of common CoO labels. Findings – Price (42 per cent), taste (40 per cent), health (18 per cent), and quality (18 per cent) were the most important factors that respondents mentioned. Only 3.5 per cent of respondents mentioned CoO as one of the factors influencing their decision. Of respondents 61 per cent, when prompted, stated that they knew the CoO of the food product selected. Of these respondents, 90 per cent were correct. Of respondents 62 per cent stated that they look at CoO labels when making food purchase decisions. Yet, only one third of respondents correctly understood the difference between the "Made in" and "Product of" labels. Research limitations/implications – The findings suggest that consumers that do access CoO labels are misinterpreting this information which may form the basis of their assumptions about the source of origin of the brands and food products they routinely purchase. Practical implications – Mandatory CoO labelling policies may add costs and reinforce misconceptions that consumers already hold about the meaning of these labels. Originality/value – This study contributes to understanding of the extent to which consumers are competent in their knowledge and understanding of these informational labels.